Examining the Effect of Thermal Treatment on the Surface Morphology and Structural Properties of Tin Dioxide Thin Films Grown Using an Economical Spray Deposition Method - Salah, Ibrahim; KALELİ, Murat and ÇORLU, Tuğba (International Journal of Computational and Experimental Science and Engineering, 2024)
Tin oxide is a versatile material that is frequently used in temperature, gas, and photo-sensing applications. It is well-known for its beneficial physical and chemical properties. This work describes an economical fabrication technique that uses an airbrush to apply SnO2 to a glass substrate in ambient circumstances. Important variables were carefully controlled, such as a constant 30 cm distance from the head of the airbrush to the preheated substrates, a 0.5 ml/minute deposition rate, and a 200 °C deposition temperature. Following that, annealing procedures were conducted at 250 and 500 °C to investigate the effects on optical, morphological, and structural characteristics. X-ray diffraction (XRD) structural investigation revealed a significant increase in crystallinity at higher annealing temperatures, with each thin film consistently displaying the rutile phase (JCPDS No. 01-0657). The produced tin dioxide thin films appear homogeneous in the images taken by the scanning electron microscope (SEM). However, there were visible structural defects. Additionally, an increase in surface roughness with higher annealing temperatures was found by atomic force microscopy (AFM) examinations. Such result holds significant value in fields like gas sensing and photon absorption, where surface properties are critical to overall performance. Finally, extensive investigations combined with the economical fabrication approach present a potential path toward customizing tin oxide thin films for a range of applications. The material’s advantage for practical applications is improved by the capacity to modify structural and morphological properties through annealing conditions, demonstrating its potential in emerging fields of technology.